The Application of Seven Tools to Improve Quality and Prevent Defects in the Instrument Panel Production Process at PT. Automotive Industry - Maspioh, Pipin; Fasa, Nadia; Dandy, Rachmad; Sumitra, Naufal Rabbani (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Product quality is an important factor in the automotive industry, because defective products can reduce production efficiency, increase costs, and reduce customer satisfaction. This study aims to identify the dominant types of defects and analyze the main causes of defects in the Instrument Panel production process at PT. Industri Otomotif by applying the Seven Tools method. The research method uses a case study approach with data collection through direct observation, interviews, and production data documentation. The analytical tools used include check sheets, flowcharts, histograms, scatter diagrams, control charts, Pareto charts, and fishbone diagrams. The results show that there are four main types of defects, namely shot mold, bubble, burry effect mold broken, and discolor (striped), with the dominant defect being shot mold at 38.52%. Further analysis using the fishbone diagram revealed that the main causes of defects come from machine, method, material, and human factors. The application of the Seven Tools has proven effective in providing a comprehensive overview of production conditions and generating improvement recommendations that can reduce the level of defects, improve product quality, and reduce production costs.